Lack of detrimental effects of ocean acidification and warming on proximate composition, fitness and energy budget of juvenile Senegalese sole (Solea senegalensis) - Oliveira, Helena (2023)
Funding Information: This work was supported by the FISHBUDGET - Effects of climate change on marine fish energy budgets ( PTDC/BIA-BMA/28630/2017 ) - project; benefited from the strategic project UIDB/04292/2020 awarded to MARE and the project LA/P/0069/2020 granted to the Associate Laboratory ARNET funded by the FCT / Ministério da Ciência, Tecnologia e Ensino Superior (MCTES), and through other national funds ( UIDB/50006/2020 ). The authors thank the Sparos, Lda company for providing the fish feed, and EPPO aquaculture research station team (Olhão) for providing juvenile fish for trails. FCT supported the contract of HO (through the FISHBUDGET project), PA (in the framework of CEECIND/01739/2017 ) and TR ( DL57/2016/CP1479/CT0023 ). Funding Information: This work was supported by the FISHBUDGET - Effects of climate change on marine fish energy budgets (PTDC/BIA-BMA/28630/2017) - project; benefited from the strategic project UIDB/04292/2020 awarded to MARE and the project LA/P/0069/2020 granted to the Associate Laboratory ARNET funded by the FCT/Ministério da Ciência, Tecnologia e Ensino Superior (MCTES), and through other national funds (UIDB/50006/2020). The authors thank the Sparos, Lda company for providing the fish feed, and EPPO aquaculture research station team (Olhão) for providing juvenile fish for trails. FCT supported the contract of HO (through the FISHBUDGET project), PA (in the framework of CEECIND/01739/2017) and TR (DL57/2016/CP1479/CT0023). Publisher Copyright: © 2022 The Authors